Internal-mesocolic hernia after laparoscopic left colectomy report of case with late manifestation. (2015) - Daskalaki, Anna; Kaimasidis, George; Xenaki, Sofia; Athanasakis, Elias; Chalkiadakis, George
Abstract: Introduction: In contrast to right colectomy, closure of the mesocolic gap after laparoscopic left colectomy is not practiced, and reports of small gut herniation through this gap are scarce. Presentation of case: A 73 year old male was admitted as an emergency with symptoms and clinical signs, suggesting obstruction of the small bowel. Abdominal imaging, including computed tomography confirmed the diagnosis. The patient had undergone laparoscopic left colectomy for cancer, three years ago. At laparotomy small bowel loops were found to herniate through the mesocolic defect at the level of the colonic anastomosis. The small bowel loops were reduced and their viability was ascertained. Because of an iatrogenic perforation of the colon at the anastomosis during small bowel loops mobilization, the colon was temporarily exteriorized in the form of a double barrel colostomy. The postoperative course was uneventful. Discussion: Very few cases have been reported in the liteature indicating the need of sutuing the mesenterium. Despite the limited numbe of the reported cases, there is clearly a risk of intenal hernia after laparoscopic left colectomy. Conclusion: Although rare internal hernia after laparoscopic left colectomy may occur, and this brings forward the question of mesocolic gap closure.